Do emergency physicians and radiologists reliably interpret pelvic radiographs obtained as part of a trauma series?. Issue 2 (12th March 2012) - Bent, Clare; Chicklore, Sugama; Newton, Alastair; Habig, Karel; Harris, Tim
Abstract : Introduction: Interpretation of pelvic radiography is an important component of the primary survey and is commonly performed by emergency physicians. Radiologists bring unique skills to trauma care, including choice of imaging modality and image interpretation. It is not clear if this limited resource is most efficiently used in the resuscitation room. No studies have compared radiologists and trauma clinicians in their ability to interpret pelvic radiographs following trauma. Objective: To determine the sensitivity and specificity of trauma experienced and trauma inexperienced emergency physicians in detecting pelvic fractures compared with radiologists, the latter subgroup combined report being used as the gold standard. Setting and methods: Prospective cohort study conducted in two large teaching hospitals in central London. All participants reviewed 144 consecutive pelvic radiographs performed each as part of a 'trauma series' and known to have undergone concomitant pelvic CT imaging. Results: No statistically significant difference was found between radiologists and emergency physicians from a trauma centre in pelvic radiograph interpretation. Radiologist reporting was associated with an improved specificity compared with emergency physicians working in a non-trauma hospital (p=0.049). The study population missed 30% of fractures on plain radiography against the gold standard of CT. Discussion: The ability to interpret trauma series pelvic radiographs is comparable between emergency physicians and radiologists. If this were also true of trauma chest radiographs, then the most valuable use of the radiologist may not be the resuscitation room but in rapid reporting of more complex imaging techniques. However, plain radiography is insensitive for pelvic fracture detection compared with CT, even in expert hands.